2023
DOI: 10.1101/2022.12.31.522405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining Cardiac Nerve Architecture During Development, Disease, and Regeneration

Abstract: Cardiac nerves regulate neonatal mouse heart regeneration and are susceptible to pathological remodeling following adult injury. Understanding cardiac nerve remodeling can lead to new strategies to promote cardiac repair. Our current understanding of cardiac nerve architecture has been limited to two-dimensional analysis. Here, we use genetic models, whole-mount imaging, and three-dimensional modeling tools to define cardiac nerve architecture and neurovascular association during development, disease, and rege… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…While both the RVOT and the aortic root contain ample ganglia plexus, 15 recent study has also highlighted the crucial role of cardiac parasympathetic nerves in ventricles. 30 Thus, our study underscores the importance of cardiac ANS imbalance in the pathophysiology of RVOT-PVCs.…”
Section: Discussionsupporting
confidence: 56%
“…While both the RVOT and the aortic root contain ample ganglia plexus, 15 recent study has also highlighted the crucial role of cardiac parasympathetic nerves in ventricles. 30 Thus, our study underscores the importance of cardiac ANS imbalance in the pathophysiology of RVOT-PVCs.…”
Section: Discussionsupporting
confidence: 56%
“…Animal models have also shown that Cxcl12 stimulates coronary repair and regeneration. Neonatal mouse heart regeneration is enabled after myocardial infarction by capillary induction of Cxcl12, which signals to artery cells and guides their migration to a location where they can form natural collateral artery bypasses that support reinnervation [48][49][50] . In adult mouse hearts, which don't regenerate, a single localized injection of CXCL12 stimulates revascularization myocardial recovery 48,51,52 .…”
Section: Discussionmentioning
confidence: 99%